Designing Design Education. An articulated programme of collective open design activities. (28th July 2017) - Collina, Luisa; Galluzzo, Laura; Maffei, Stefano; Monna, Vanessa
Abstract: Design Education is changing. Setting out from the awareness that "the profile of design professions need not – and should not – remain what it is today" (Findeli, 2001, p.17) and from insight suggesting that the "experimental approach will become the "normal" approach in our future" (Manzini, 2015, p.54), the authors worked on an articulated programme of collective open design activities reflecting these changes. The activities focus on concrete experimentation on the paradigm of distributed production, which modifies the articulation of known roles and the traditional design education approaches. Therefore, the initiative aims at involving important international design schools in a concrete design exploration of this key issue for society and the design discipline itself. Manzini (2015) urged to "look at the whole of society as a huge laboratory of sociotechnical experimentation": this practice is a remarkable example which may be used as a model in the future on a larger scale.